(-33)=(-17)-n

Simple and best practice solution for (-33)=(-17)-n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-33)=(-17)-n equation:


Simplifying
(-33) = (-17) + -1n
-33 = (-17) + -1n
-33 = -17 + -1n

Solving
-33 = -17 + -1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'n' to each side of the equation.
-33 + n = -17 + -1n + n

Combine like terms: -1n + n = 0
-33 + n = -17 + 0
-33 + n = -17

Add '33' to each side of the equation.
-33 + 33 + n = -17 + 33

Combine like terms: -33 + 33 = 0
0 + n = -17 + 33
n = -17 + 33

Combine like terms: -17 + 33 = 16
n = 16

Simplifying
n = 16

See similar equations:

| (-33)=(-17)-n | | 21+21j+j+19j=125+2j | | -11m+3m=12-44 | | 2p^2+15p+13=0 | | 4t+4t=15+2-9 | | 3z=5z-24 | | 4(-6r-2)-2=-130 | | =2.44444444 | | 17x+1=-14 | | 1x-9=6 | | 8x+12y=1024 | | f(5)-f(3)= | | 2w+2.5=0.25w | | F(4)=3c | | y=(-0.5)x^2+140 | | 2(-2)+3(5)= | | .02x+.03y=-5 | | 6x^3+54x^2+120x=0 | | 3n-8n=40 | | 7+2(5n+3)-n= | | 2(3x-4)-36= | | 12+3(2y+4)= | | 8+2(3y+4)= | | 3(8-x)-36=21x-4(3+6x) | | -2p+9+3p=18 | | 2p^2+15p+22=0 | | x+62=90 | | 6+8x=2(4x+4) | | 2(x+3)(x+3)-9=89 | | 2p^2+15p=22 | | A=4a+6 | | 3y+2x-7= |

Equations solver categories